Advances in the treatment of NASH - Adams, Leon (Henry Stewart Talks, 2019)
Treatment & prognosis of patients with NAFLD, Dietary therapy and NAFLD, Efficacy of bariatric surgery, Exercise and NAFLD, Current drug treatments for NAFLD and their efficacy, Drugs that are in development with a combination of anti-metabolic and anti-inflammatory/fibrotic agents likely to be most efficacious, Methods for assessing a patient’s response to treatments